Alterations in follicular fluid BMP-15 RNA expression in women undergoing controlled ovarian hyperstimulation - Deveci, Sukriye Derya (Tubitak Scientific & Technological Research Council Turkey, 2020)
Background/aim: Bone morphogenetic protein-15 (BMP-15) is one of the maturation indicators of the ovarian follicular pool. The aim of this study was to investigate the possible difference of follicular fluid (FF) BMP-15 RNA expression among low, normal, and high responder women attending controlled ovarian hyperstimulation-intracytoplasmic sperm injection (COH-ICSI) cycles. Materials and methods: This cross-sectional study was conducted with 75 FFs of COH-ICSI cycles performed at the IVF Unit of University Hospital. Twenty FF from low response (group 1), 27 FF from normal response (group 2), and 28 FF from high response (group 3) were recruited for the study between September 2014 and February 2015. Cycle parameters were collected from patient files. FF BMP-15 RNA expression was evaluated with real-time polymerase chain reaction analysis. Statistical analysis was done with SPSS 16.0 version (SPSS Chicago, IL, USA). Results: The mean age, infertility duration, and body mass index (BMI) of patients were 31.1 +/- 4.4 years, 7.4 +/- 4.5 years, and 25.6 +/- 4.1 kg/m(2), respectively. There was no significant difference among groups for age, infertility duration, and BMI. There was no significant difference among groups for fertilization rate, implantation rate, pregnancy rate, and live birth rate. Among the 3 groups, FF BMP-15 RNA overexpression and lower expression rates were not significantly different. In all groups, overexpression showed dominance. The pregnancy rate was 45% among women with lower expression and the pregnancy rate among women with overexpression was 26% (P = 0.02). BMP-15 overexpression showed impact on becoming pregnant (OR = 3.7, 95% CI = 1.245-11.299, P = 0.019). Conclusion: In this study, there was no significant difference in FP BMP-15 RNA expression levels among low, normal, and high responder women. However, overexpression of FF BMP-15 RNA showed a negative impact on pregnancy rates of women who attended COH-ICSI cycles.
Keywords: Follicular fluid; BMP-15; RNA expression; assisted reproduction; oocyte